HUBUNGAN PENGETAHUAN DAN DUKUNGAN SOSIAL TERHADAP SKOR KEPATUHAN MINUM OBAT KELASI BESI PADA PASIEN THALASSEMIA (Studi di RSUD Tidar Kota MageIang) - Widia Adiratna; Ari Udiyono; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2020)
Adherence to treatment is a big challenge for thalassemia patients. Iron chelation is one of treatment that must be carried out by thalassemia patients for preventing complications due to iron accumulation in the body's organs. Most of the deaths in thalassemia patients are caused by complications due to accumulation of iron from blood transfusions. Adherence to iron chelation treatment is a protective factor for thalassemia mortality. The objective of the study is to analyze the reIationship between knowledge and social support with adherence score to iron cheIation treatment in thaIassemia patients. This study uses a quantitative method with a cross-sectionalI approach, the data obtained were 84 respondents. Primary data was collected by interview using a questionnaire. The statistical test used was Pearson correlation. The resuIts of bivariate anaIysis show that age knowledge about thalassemia (p=0,000;r=0,491-0,554), knowIedge about  iron cheIation (p=0,000;r=0,554), famiIy support (p=0,000;r=0,570), and health workers support (p=0,000; r=0,468). It can be concluded that knowledge about thaIassemia, knowIedge about iron cheIation, famiIy support, heaIth workers support, have a significant relationship with adherence score to taking iron chelation in thaIassemia patient. Keywords: adherence, iron chelation, thalassemia